2021
DOI: 10.3390/pr9122260
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Dynamic Characteristics for Machine Tools Based on Dynamic Stiffness Sensitivity

Abstract: Dynamic parameters are the intermediate information of the entirety of machine dynamics. The differences between components have not been combined with the structural vibration in the cutting process, so it is difficult to directly represent the dynamic characteristics of the whole machine related to spatial position. This paper presents a method to identify sensitive parts according to the dynamic stiffness-sensitivity algorithm, which represents the dynamic characteristics of the whole machine tool. In this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…The extracted features are employed to investigate the information pertaining to the future time. The vibration data of a machine tool are used to illustrate the dynamic characteristics of the machine [32]. The amplitude of vibrations in different states exhibit a varying temporal profile (Figure 13).…”
Section: Data Acquisitionmentioning
confidence: 99%
“…The extracted features are employed to investigate the information pertaining to the future time. The vibration data of a machine tool are used to illustrate the dynamic characteristics of the machine [32]. The amplitude of vibrations in different states exhibit a varying temporal profile (Figure 13).…”
Section: Data Acquisitionmentioning
confidence: 99%
“…When subjected to complicated external dynamic loads, joint component substructures are prone to micro-vibration with multi-directional degrees of freedom (DOFs). The joints will be able to show off the crucial characteristic of flexible connections by storing and dissipating energy and demonstrating elasticity and damping [57][58][59]. Statistics indicated that joint factors like damping and stiffness account for 30% to 50% of stiffness and 90% of the CNCMT's dynamic performance damping.…”
Section: Major Identification Elementmentioning
confidence: 99%
“…Hence, it was considered to be a sensitive part of the holistic VMC to enhance the dynamics through stiffness improvement and mass reduction. 33 Further, limited results of investigations have been reported for the design and analysis of spindle head built with alternate materials. In the present work, the CI spindle head of the VMC depicted in Figure 1 is replaced with steel-reinforced EG with the objective of improving the dynamic performance of the spindle head which in turn improves the overall dynamics of VMC.…”
Section: Introductionmentioning
confidence: 99%